Interação lectina-neomicina de Dioclea violacea e seu efeito modulador contra cepas multirresistentes promove a purificação do antibiótico em coluna de lectina imobilizada - SANTOS, Maria Helena Cruz dos (2022)
The World Health Organization has established bacterial resistance to antibiotics as one of the most important threats to public health in the XXI century, making it necessary to develop new strategies for the use of antibiotics in order to mitigate the consequences of this problem. Studies have highlighted a class of proteins that recognize and interact with specific carbohydrates called lectins, these have several biological activities, among them its modulating effect on the activity of antibiotics against multidrug-resistant pathogens. Neomycin is a bactericidal aminoglycoside that inhibits protein synthesis in Gram-negative and Gram-positive bacteria. The combination of lectins with neomycin may be able to increase the antibacterial effect of the aminoglycoside, thus proving to be a potential biotechnological tool. This study aimed to evaluate whether Dioclea violacea lectin (DVL) has the ability to interact with neomycin via the carbohydrate recognition domain and to modulate the antibiotic activity of neomycin in multidrug-resistant bacteria. The lectin was purified from affinity chromatography and used in the hemagglutinating activity inhibition assays with neomycin and antibacterial assays. Assays were performed to evaluate the interactions of column-immobilized neomycin-DVL -Sepharose® 4B. The hemagglutinating activity test revealed that neomycin inhibited the hemagglutinating activity of DVL with a minimum inhibitory concentration of 50 mM, indicating that the antibiotic interacts with DVL via the carbohydrate recognition domain. The DVL immobilized on Sepharose® 4B activated by cyanogen bromide bound 41% of the total neomycin applied to the column, indicating that the DVL-neomycin interaction is efficient for purification processes. The MIC (Minimum Inhibitory Concentration) for the antibacterial activity obtained for DVL against all strains studied was not observed at MIC ≥ 1024 μg/mL. However, when DVL was combined with neomycin, a significant increase in antibiotic activity was observed against Staphylococcus aureus and Pseudomonas aeruginosa. These results demonstrate the first report of lectin-neomycin interaction, indicating that immobilized DVL has the potential to isolate neomycin by affinity chromatography. In addition, DVL increased the antibiotic activity of neomycin against multidrug-resistant (MDR) strains, suggesting that it is a potent adjunct in the treatment of infectious diseases.